Elevated CO2 enhanced water use efficiency of wheat to progressive drought stress but not on maize - Cao, Qingjun; Li, Gang; Liu, Fulai (Frontiers in Plant Science, 2022)
Global rising atmospheric CO2 concentration ([CO2]) and drought stress exert profound influences on crop growth and yield. The objective of the present study was to investigate the responses of leaf gas exchange and plant water use efficiency (WUE) of wheat (C3) and maize (C4) plants to progressive drought stress under ambient (a[CO2], 400 ppm) and elevated (e[CO2], 800 ppm) atmospheric CO2 concentrations. The fraction of transpirable soil water (FTSW) was used to evaluate soil water status in the pots. Under non-drought stress, e[CO2] increased the net photosynthetic rate (An) solely in wheat, and dry matter accumulation (DMA), whereas it decreased stomatal conductance (gs) and water consumption (WC), resulting in enhanced WUE by 27.82% for maize and 49.86% for wheat. After onset of progressive soil drying, maize plants in e[CO2] showed lower FTSW thresholds than wheat, at which e.g. gs (0.31 vs 0.40) and leaf relative water content (0.21 vs 0.43) starts to decrease, indicating e[CO2] conferred a greater drought resistance in maize. Under the combination of e[CO2] and drought stress, enhanced WUE was solely found in wheat, which is mainly associated with increased DMA and unaffected WC. These varied responses of leaf gas exchange and WUE between the two species to combined drought and e[CO2] suggest that specific water management strategies should be developed to optimize crop WUE for different species in a future drier and CO2-enriched environment.